Religiosity and its Relationship with Smoking Cessation: A Systematic Review. - Azmi, Junainah; Munirah, Sharifah; Nurumal, Mohd Said; Hani , Hanida (IIUM Medical Journal Malaysia, 2021)
Objective: This study aims to systematically review the literature regarding the relationship between religiosity and smoking behaviour. Methods: Four electronic databases were used to identify the literatures including Scopus, Science Direct, ProQuest and PubMed. The search was limited to full text articles and in English or Malay only. Articles on smoking prevention and other nicotine delivering devices such as vape or electronic cigarette were excluded from the study. Results: Initially, 10,154 articles were retrieved and 12 met the inclusion criteria. Out of the 12 studies, five studies revealed a significant relationship between religious activities and cessation while the others showed inverse associations between religiosity and smoking. Conclusion: Religiosity played an important role in influencing smoking behaviour, making it an important vehicle to complement other existing tobacco control efforts. Limited studies were focusing on the Islamic religion despite the growing number of Muslim populations worldwide. Thus, further research on the integration of Islamic religion in smoking cessation program is highly recommended especially in a Muslim country like Malaysia.